Oxidation of norbornene over vanadium-substituted phosphomolybdic acid catalysts and spectroscopic investigations - Raj, N. K. K.; Ramaswamy, A.; Manikandan, Palanichamy (Journal of Molecular Catalysis A-Chemical, 2005)
Oxidation of norbornene has been carried out over mono-, di- and tri-vanadium-substituted phosphomolybdic acid catalysts with aqueous hydrogen peroxide (aq. H2O2) as an oxidant in different solvents. Monovanadium-substituted phosphomolybdic acid catalyst was found to be better than other catalysts for the above reaction and acetonitrile was the suitable solvent. At the optimum temperature of 60 degreesC, the norbornene conversion was 70% and the selectivity for 2,3-epoxy norbornane was 58%. The side products were norborneols and 2-norbornanone. The lower selectivity of 2,3-epoxy norbornane with aq. H2O2 is attributed to the simultaneous formation of other products, norborneols and 2-norbornanone. The norborneols are formed from norbornene by acid-catalyzed reaction. Other oxidants like urea-hydrogen peroxide adduct (UHP) and tert-butyl hydrogen peroxide (TBHP) were also tested for norbornene oxidation reaction. With UHP, the conversion was almost same (69%) as that of aq. H2O2 reaction; however, 2,3-epoxy norbornane was the main product with >97% selectivity. Thus, the overall yield was 66.9% at 60 degreesC after 4 h. The high selectivity with UHP is attributed to the controlled release of H2O2, absence of water and less acidic nature of UHP. With TBHP the selectivity for the epoxide was >96%; however, the conversion was low (27%). A mechanism for the norbornene oxidation is believed to be proceeding via V(5+)-peroxo and V(4+)-superoxo intermediates. NMR, EPR and UV-vis spectroscopic techniques were employed to understand the reaction intermediates and reaction pathways. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: 2; 3-epoxy norbornane; aq. H2O2; epoxidation; EPR; NMR; norbornene; urea-H2O2 adduct; UV-Vis; vanadium-substituted phosphomolybdic acid

Vanadium-containing ordered mesoporous silicates: does the silica source really affect the catalytic activity, structural stability, and nature of vanadium sites in V-MCM-41? - Shylesh, S; Singh, AP (Journal of Catalysis, 2005)
A series of vanadium-substituted mesoporous materials were synthesized hydrothermally with the use of two commonly used silica Sources. fumed silica and tetra ethyl orthosilicate. The extent of mesopore structural ordering was confirmed from X-ray diffraction, N-2 physisorption, SEM, and TEM, and the presence and nature of vanadium species inside the framework of the MCM-41 matrix was confirmed in detail with the use of various characterization techniques like FT-IR, Si-29 MAS NMR, DRUV-vis, EPR, V-51 MAS NMR, and Raman analysis. It is deduced from the above characterization techniques that, regardless of the silica source, vanadium is incorporated into the silica framework and thereby increases the structural ordering and wall thickness of the mesoporous material. Thermal and hydrothermal Studies performed over the V-MCM-41 catalysts show that the Si-O-Si inorganic backbone from a fumed silica source is more resistant to severe thermal treatments and hydrolysis than the tetraethyl orthosilicate-synthesized catalysts. Spectroscopic characterization reveals the existence of easily accessible isolated tetrahedral vanadium sites on V-MCM-41 catalyst prepared front fumed silica catalyst, whereas the sample obtained from a tetraethyl orthosilicate silica Source shows vanadium in more disordered sites. Catalytic results show that both catalysts display excellent activity toward the epoxidation reaction of bulkier olefins, and the exceptional activity of the fumed silica catalyst may arise from the more isolated tetrahedral sites and the complementary textural characteristics, which may facilitate the easy access of substrate to the isolated framework metal sites. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: epoxidation; fumed silica; MCM-41; tetraethyl orthosilicate; Vanadium

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone, novel cytokine modulators via sharpless asymmetric epoxidation and L-proline catalyzed mannich reaction - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron, 2006)
A short and efficient enantioselective synthesis of (-)-cytoxazone and its stereoisomer (+)-epi-cytoxazone, novel cytokine modulators, has been described with good yield and enantioselectivity. Ti-catalyzed Sharpless asymmetric epoxidation of allyl alcohol and L-proline catalyzed three-component Mannich reaction constitute the key steps in introducing stereogenicity into the molecule. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Asymmetric synthesis; epoxidation; Mannich reaction; Oxidation; Ozonolysis

Vanadium-containing ethane-silica hybrid periodic mesoporous organosilicas: synthesis, structural characterization and catalytic applications - Shylesh, S.; Singh, A. P. (Microporous and Mesoporous Materials, 2006)
Vanadium-containing ethane-silica hybrid mesoporous silsesquioxane materials (V-HMM) with uniform hexagonal arrangement were prepared using C-18-, C-16- and C-14-alkyl trimethyl ammonium (ATMA) surfactants under basic conditions. The materials were characterized by PXRD, N-2 adsorption-desorption, UV-Visible spectroscopy, Raman, Si-29, C-13 and V-51 solid-state MAS NMR, TEM and SEM techniques. The characterization techniques revealed that the structural ordering, morphology as well as the percentage of metal incorporation depends strongly on the hydrophobic chain length of the surfactant. PXRD, electron microscopy and N-2 adsorptiondesorption analysis confirmed that the original hexagonal structure of the material is maintained after vanadium substitution. UV-Visible, V-51 NMR and Raman analysis certified that vanadium exists in a highly dispersed state and had tetrahedral coordination with the support surface. Liquid-phase epoxidation reaction of styrene using aqueous H2O2 and TBHP as oxidants, showed that the hybrid materials were highly active and more stable than conventional vanadosilicates. The high catalytic activity and improved epoxide selectivity of the V-HMM samples is related to the more hydrophobic environment inside the pore channels than the silica channels in V-MCM-41. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: epoxidation; organo vanadosilicates; styrene; V-HMM; V-MCM-41

Eco-friendly synthesis of epichlorohydrin catalyzed by titanium silicate (TS-1) molecular sieve and hydrogen peroxide - Pandey, Rajesh Kumar; Kumar, Rajiv (Catalysis Communications, 2007)
In a mixed solvent system of acetonitrile and methanol, titanium silicate molecular sieve, TS-1, having MFI topology, efficiently catalyses the epoxidation of allyl chloride to the corresponding epichlorohydrin in excellent yields using dilute hydrogen peroxide (45%) as an oxidizing agent. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: allyl chloride; epichlorohydrin; epoxidation; heterogeneous catalysis; selectivity; titanium silicalite-1

Expeditious assembly of 3,4-benzannulated 8-oxabicyclo[3.2.1]octane systems by [2+2+2] alkyne cyclotrimerisation: Total synthesis of (-)-bruguierol A - Ramana, Chepuri V.; Salian, Sumanth R.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2007)
Facile construction of benzene-fused 8-oxabicyclo[3.2.1]octane systems by employing a cross alkyne cyclotrimerisation reaction was explored. With this procedure, (-)-bruguierol A was synthesised, and its absolute configuration was established.
Keywords: cyclotrimerisation; epoxidation; Total synthesis; Wilkinson's catalyst

Short and efficient synthetic strategy for the total syntheses of (S)-(+)- and (R)-(-)-Plakolide A - Mohapatra, Debendra K.; Pramanik, Chintnoy; Chorghade, Mukund S.; Gurjar, Mukund K. (European Journal of Organic Chemistry, 2007)
Concise and efficient total syntheses of anticancer agents (S)(+)-Plakolide A and (R)-(-)-Plakolide A were accomplished in eight steps and an overall yield of 39 % starting from geraniol. The key steps in our strategy are Sharpless asymmetric epoxidation, double elimination, and Stille coupling reactions.
Keywords: Cross-coupling; epoxidation; inhibitors; olefination

Spectroscopic and catalytic properties of SBA-15 molecular sieves functionalized with acidic and basic moieties - Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2007)
SBA-15, grafted with Lewis acidic Ti4+ ions and basic amines (imidazole, guanine or adenine) exhibited high catalytic activity in the cycloaddition of CO2 to epoxides yielding selectively cyclic carbonate precursors of polycarbonates. In the second class of materials, the surface of SBA-15 was grafted with thiol or sulfonic acid functionalities. Mn(Salen)Cl was, then, covalently bound to these acidic groups. The resulting catalysts show enhanced chemo-, regio- and stereo-selective catalytic activity in the epoxidation of terpenes such as R-(+)limonene, alpha-pinene and Delta-carene with molecular oxygen. The acid-base properties of these modified SBA- 15 materials were investigated by temperature-programmed desorption and diffuse-reflectance infrared Fourier transform spectroscopy. Ammonia and pyridine were used as probe molecules for acidic sites and CO2 for basic sites. Acidic Ti sites activated epoxides and the grafted basic amines activated CO2. The simultaneous presence of both acidic and basic sites on amine/adenine-functionalized Ti-SBA-15 enabled synergistic enhancement in catalytic activity in the cycloaddition reaction of CO2 to epoxides. When Mn(Salen)Cl was immobilized on thiol or sulfonic acid-functionalized SBA-15, the oxidation state of Mn decreased from +3 to +2. The organo-acidic functional groups (thiol or sulfonic acid) axialk, coordinated to Mn ions modified the electronic structure of Mn ions enhancing the activity and selectivity of Mn(Salen) complexes in aerial oxidation reactions. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aerial oxidation of terpenes; CO2 utilization; cyclic carbonates synthesis; epoxidation; functionalization with acidic and basic moieties; immobilization of Mn complexes; organo-functionalization of SBA-15; solid acid-base catalysts

Supported copper oxide as a highly active/selective catalyst for the epoxidation of styrene by TBHP to styrene oxide - Choudhary, Vasant R.; Jha, Rani; Chaudhari, Nitin K.; Jana, Prabhas (Catalysis Communications, 2007)
Liquid phase epoxidation of styrene by anhydrous and aqueous TBHP to styrene oxide has been studied under reflux, using different supported CuO (viz. Cuo/Si-MCM-41, CuO/Al2O3, CuO/Ga2O3 and CuO/In2O3) as easily separable and reusable heterogeneous catalysts. The CuO/Ga2O3 catalyst showed the best performance in the epoxidation by aqueous TBHP. The CuO supported on In2O3 or Si-MCM-41 also showed very good performance in the epoxidation but only by anhydrous TBHP. However, the CUO/SiO2 catalyst, however, showed very good performance in the epoxidation by both the anhydrous and aqueous TBHP. Influence of the reaction conditions (temperature, time and TBHP/styrene ratio) on the epoxidation by aqueous TBHP over the best catalyst (CuO/Ga2O3) has been investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CuO/Al2O3; CuO/Ga2O3; CuO/In2O3; Cuo/Si-MCM-41; CuO/SiO2; epoxidation; styrene; Styrene oxide; tertiary butyl hydroperoxide

Alkene epoxidation catalyzed by vanadomolybdophosphoric acids supported on hydrated titania - Ingle, Rohit H.; Vinu, A.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Vanadomolybdophosphoric acids wet-impregnated oil hydrated titania (TiO(2) - xH(2)O), make ail efficient catalytic system for the epoxidation of a variety of alkenes with organic solvent extracted TBHP as the oxidant. By,in appropriate choice of solvent, the catalyst call be reused at least three times without much loss in the activity for subsequent runs. XRD shows that the heteropoly acid is uniformly dispersed over the support and up to 15 wt% loading of the heteropoly acid, no additional peak of the same call be seen in the XRD pattern of the catalyst. The reactivity varied with the nature of alkene but the major product was always the corresponding epoxide. The catalytic system is free of high temperature calcination steps and tedious multi-step procedures, normally encountered in the heter-ogenization of heteropoly acids. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkenes; epoxidation; heteropoly acids; TBHP; titania; vanadomolybdophosphoric acids

First asymmetric total synthesis of penarolide sulfate A(1) - Mohapatra, Debendra K.; Bhattasali, Debabrata; Gujar, Mukund K.; Khan, Mohammad Islam; Shashidhara, K. S. (European Journal of Organic Chemistry, 2008)
Penarolide sulfate A(1), with three contiguous stereogenic centers on a macrocyclic skeleton, affords promise as an alpha-glucosidase inhibitor. Herein, we describe the first asymmetric total synthesis of this natural product. A stereoselective strategy for rapid assembly of the complete framework of the 30-membered macrocyclic core is delineated herein. Sequential amidation and intramolecular Sonogashira cross-coupling reactions were pivotal to the success of our efforts. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Asymmetric synthesis; C-C coupling; Dihydroxylation; epoxidation; Macrocycles; Regioselectivity; Total synthesis

Lacunary Keggin type polyoxotungstates in conjunction with a phase transfer catalyst: an effective catalyst system for epoxidation of alkenes with aqueous H2O2 - Ingle, Rohit H.; Raj, N. K. Kala (Journal of Molecular Catalysis A-Chemical, 2008)
Na-9[SbW9O33] in conjunction with a phase transfer catalyst (methyl tricapryl ammonium chloride) is a highly efficient catalytic system for the selective epoxidation of alkenes with aqueous H2O2 as the oxidant. Importantly, the reactions can be carried out in the absence of any organic solvents. The alkene epoxidation reactions with both, a transition metal ion substituted polyoxotungstate as well as a transition metal ion free polyoxotungstate precursor indicates that the tungstate group is the active center for the oxidation reaction. It was also observed that the transition metal ion does not play any significant role in the reaction. IR studies support the formation of tungsten-peroxo species and also show that the catalyst is stable in the presence of phase transfer catalyst when aqueous H2O2 is used as an oxidant. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alkenes; Aqueous H2O2; epoxidation; Na-9[SbW9O33]; Phase transfer catalyst; polyoxometalates

Periodic mesoporous silicas and organosilicas: an overview towards catalysis - Shylesh, S.; Samuel, Prinson P.; Sisodiya, Sheetal; Singh, A. P. (Catalysis Surveys from Asia, 2008)
Micelle-templated mesoporous and organic-inorganic hybrid mesoporous materials are important in many fields of material research, especially for hosting catalysts in confined space. Among this class, the recent discovery of periodic mesoporous organosilicas (PMOs) represent an exciting new group of organic-inorganic nanocomposites targeted for a broad range of applications ranging from catalysis to microelectronics. Compared to the earlier generation of organic-inorganic hybrid mesoporous samples, obtained by the cocondensation reaction or by the grafting reaction, PMOs represent the right combination of organic and inorganic groups in the frame wall positions. This article reviews the current state of art in organic-inorganic hybrid mesoporous material research with special emphasis over periodic mesoporous organosilica materials having various redox centers (Ti, V, Cr) suitable for oxidation reactions as well as acidic sites (Al, -SO(3)H) for the organic transformation of bulky molecules.
Keywords: Acid catalysis; epoxidation; Mesoporous organosilicas; Organic-inorganic hybrid materials

Selective epoxidation of styrene to styrene oxide by TBHP using simple transition metal oxides (NiO, CoO or MoO3) as highly active environmentally-friendly catalyst - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Catalysis Communications, 2008)
Simple transition metal oxides, such as NiO, CoO or MoO3, etc. show high catalytic activity for the selective epoxidation of styrene to styrene oxide by TBHP. The order of choice for different transition metal oxides for epoxidation is NiO > CoO > MoO3 > Cr2O3 > Fe2O3 > ZnO >= U3O8 >> TiO2 >> MnO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CoO; epoxidation; MoO3; NiO; styrene; Styrene oxide; TBHP

Supported nano-gold catalysts for epoxidation of styrene and oxidation of benzyl alcohol to benzaldehyde - Choudhary, Vasant R.; Dumbre, Deepa K. (Topics in Catalysis, 2009)
Nano-gold particles supported on different alkaline earth oxides (viz. MgO, CaO, BaO and SrO), Gr. IIIa metal oxides (viz. Al(2)O(3), Ga(2)O(3), In(2)O(3) and Tl(2)O(3)), transition metal oxides (viz. TiO(2), Cr(2)O(3), MnO(2), Fe(2)O(3), CoO(x), NiO, CuO, ZnO, Y(2)O(3) and ZrO(2)), rare earth metal oxides (viz. La(2)O(3), Ce(2)O(3), Nd(2)O(3), Sm(2)O(3), Eu(2)O(3), Tb(2)O(3), Er(2)O(3) and Yb(2)O(3)) and U(3)O(8) [all prepared by depositing gold on corresponding metal oxide support by deposition precipitation (DP) and/or homogeneous deposition precipitation (HDP) method] were evaluated for their catalytic performance in the liquid phase epoxidation of styrene by tert-butyl hydroperoxide (TBHP) to styrene oxide and also in the solvent-free benzyl alcohol-to-benzaldehyde oxidation (by molecular oxygen or TBHP) reactions. For the epoxidation, the catalytic performance (styrene oxide yield) of the most promising nano-gold catalysts prepared by the HDP method was in the following order: Au/MgO > Au/Tl(2)O(3) > Au/Yb(2)O(3) > Au/Tb(2)O(3) > Au/CaO (or TiO(2)). However, for the oxidation of benzyl alcohol to benzaldehyde by molecular oxygen, the order of choice for the most promising catalysts (based on benzaldehyde yield) was Au/U(3)O(8) > Au/Al(2)O(3) > Au/ZrO(2) > Au/MgO. Whereas, when TBHP was used as an oxidizing agent for the benzyl alcohol oxidation, the order of choice for the most promising catalysts was Au/U(3)O(8) > Au/MgO > Au/TiO(2) > Au/ZrO(2) > Au/Al(2)O(3). The catalytic performance of a particular supported nano-gold catalyst was thus found to depend on the reaction catalysed by them. Moreover, it is strongly influenced by a number of catalyst parameters, such as the metal oxide support, the method of gold depositon on the support, the gold loading and also on the catalyst calcination temperature. Nano-gold particles-support interactions seem to play an important role in controlling the deposition of gold ( amount of gold deposited and size and morphology of gold particles), formation of different surface gold species (Au(0), Au(1+) and Au(3+)) and electronic properties of gold particles and, consequently, control the catalytic performance (both the activity and selectivity) of the supported nano-gold catalysts in the reactions. The nano-gold catalysts prepared by the HDP method showed much better catalytic performance than those prepared by the DP, coprecipitation or impregnation method; in general, the HDP method provided supported gold catalysts with much higher gold loading and/or smaller size gold particles than that achieved by the DP and other methods.
Keywords: Benzaldehyde; Benzyl alcohol; epoxidation; Metal oxide supports; Nano-gold catalysts; Oxidation; styrene; Styrene oxide

Kinetics studies and mechanism evolution of the epoxidation of styrene over nanoporous Au doped TS-1 - Saxena, Samidha; Dwivedi, Reena; Bhadauria, Sheenu; Chumbhale, Vilas R.; Prasad, Rajendra (Polish Journal of Chemical Technology, 2010)
{A kinetic investigation of the slurry phase epoxidation of styrene with hydrogen peroxide has been carried out, for the first time, over nanoporous Au doped TS-1 catalyst, in a batch reactor, in the temperature range of 313-333 K. It was found that product selectivity and the rate of reaction are greatly influenced by concentrations of styrene and hydrogen peroxide. Kinetics studies reveal that the mechanism of the reaction is of the ``Redox'' type. The rate equation
Keywords: Au/TS-1; epoxidation; kinetics; styrene; Styrene oxide

Selective epoxidation of methyl soyate over alumina-supported group VI metal oxide catalysts - Satyarthi, Jitendra K.; Srinivas, D. (Applied Catalysis A-General, 2011)
Epoxidation of methyl soyate (biodiesel), soybean oil and oleic acid with tert.-butyl hydroperoxide (TBHP) was investigated over gamma-alumina-supported group VI metal oxides (CrOx/Al2O3, MoOx/Al2O3 and WOx/Al2O3) prepared by impregnation method. The studies revealed that 15 wt% MoOx on gamma-Al2O3 was the most active catalyst (conversion >90 mol% under optimized conditions). While MoOx/Al2O3 is selective mainly for epoxidation, the other catalysts are active for epoxidation as well as for decomposition of TBHP. The active species on the catalyst surface were investigated using in situ UV-visible spectroscopy. A linear correlation was observed between epoxidation activity and surface acidity of the catalyst. A new H-1 NMR method was developed to monitor the progress of epoxidation reaction which was found to be superior to gas chromatographic method in estimating the conversion of double bonds of fatty compounds. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alumina-supported group VI metal oxides; Biodiesel; epoxidation; Fatty acids; H-1 NMR spectroscopy; MoOx/Al2O3; Vegetable oil

Tin incorporated periodic mesoporous organosilicas (Sn-PMOs): synthesis, characterization, and catalytic activity in the epoxidation reaction of olefins - Sisodiya, Sheetal; Shylesh, S.; Singh, A. P. (Catalysis Communications, 2011)
Tin incorporated mesoporous organosilicas (Sn-PMO) having uniform hexagonal arrangements were prepared using alkyl trimethylammonium bromide surfactants under basic reaction conditions. Characterization techniques revealed that the structural ordering, morphology, and the percentage of tin incorporation depend critically on the hydrophobic chain length of surfactants. The Sn-PMO samples are thermally stable up to 500 degrees C under air atmosphere and were hydrothermally stable up to 100 h in boiling water. The organotinsilicates showed excellent catalytic activity and reusability in the epoxidation of norbornene and ciscyclooctene than an Sn-MCM-41 due to organic groups in the frame wall positions and the better accessibility of reactants to the active sites. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: epoxidation; Hydrothermal stability; Mesoporous; Organosilica; Sn-MCM-41; Sn-PMO

Molybdenum(VI) dioxo complexes for the epoxidation of allylic alcohols and olefins - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Shubhangi B. Umbarkar; Michon, Christophe; Agbossou-Niedercorn, Francine (Journal of Organometallic Chemistry, 2014)
Several molybdenum(VI) dioxo complexes have been investigated as catalyst precursors for allylic alcohol epoxidation using mainly hydrogen peroxide as oxidant. All catalysts proved to be efficient and selective for the epoxidation of allylic alcohols provided the olefins were rather electron rich. Indeed, electron poor substrates could be converted selectively into the corresponding unsaturated aldehydes. A chiral dioxomolybdenum complex based on an optically pure tridentate Schiff base ligand was synthesized and characterized. Though that complex provided an efficient epoxidation catalyst for allylic alcohols and olefins, no chiral induction was observed. During the X-ray diffraction analysis, the cooling at 100 K led to the appearance of super-lattice reflections on diffraction patterns reflecting an ordering of the structure. Instead of one organometallic species observed at 298 K, three similar complexes of the same molecular structure could be observed in the asymmetric unit at 100 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allylic alcohol; epoxidation; Molybdenum; Oxidation; Peroxide

N-Heterocyclic carbene catalyzed oxidative coupling of alkenes/alpha-bromoacetophenones with aldehydes: a facile entry to alpha,beta-epoxy ketones - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Angewandte Chemie-International Edition, 2015)
{A novel, N-heterocyclic carbene (NHC) catalyzed direct oxidative coupling of styrenes with aldehydes has been described for the synthesis of alpha,beta-epoxy ketones in good yields. This unprecedented regioselective oxidative coupling employs NBS/DBU/DMSO (DBU = 1,8-diazabicyclo [5.4. 0] undec-7-ene
Keywords: aldehydes; epoxidation; N-heterocyclic carbenes; Oxidation; synthetic methods

Environmentally benign bioderived carbon microspheres-supported molybdena nanoparticles as catalyst for the epoxidation reaction - Doke, Dhananjay S.; Umbarkar, Shubhangi B.; Gawande, Manoj B.; Zbori, Radek; Biradar, Ankush V. (ACS Sustainable Chemistry & Engineering, 2017)
A one pot synthesis of molybdenum oxide nanoparticles (NPs supported on bioderived carbon microspheres is reported. The catalyst was synthesized by the low temperature hydrothermal (LTH) method using D-glucose and bagasse as the carbon source. The carbonization of bagasse resulted in the formation of nonuniform carbon microspheres while glucose resulted in uniform carbon spheres. SEM and STEM elemental mapping show the uniform distribution of molybdenum oxide NPs over the carbon microspheres. XPS spectroscopy confirmed that molybdenum was in the Mo6+ oxidation state. The 1% MoO3 supported on carbon microspheres derived from D-glucose showed excellent catalytic activity up to 100% olefin conversion with 100% epoxide selectivity using organic tent-butyl hydroperoxide as an oxidant. The catalyst was successfully used for up to five cycles without losing substantial activity and selectivity.
Keywords: Carbon microspheres; epoxidation; heterogeneous catalysis; Hydrothermal synthesis; TBHP

Subtle interaction between Ag and O 2 : a near ambient pressure UV photoelectron spectroscopy (NAP-UPS) investigations - Ghosalya, Manoj Kumar (Journal of Chemical Sciences, 2018)
The Ag-O2 interaction, which is at the center-stage of Ag-catalyzed partial oxidation reactions, is studied with NAP-UPS up to 0.2 mbar O2 pressure between 295 and 550 K. Three temperature regimes were identified for distinct Ag-O2 interaction, which are (a) 295–390 K, where mainly dissociative chemisorption of O2 happens, (b) 390–450 K, where diffusion of O-atoms into the sub-surfaces of Ag is prominent, and (c) >450 K, where metastable oxide forms on polycrystalline Ag surfaces. The work function (WF) of Ag changed from 4.95 (≤390 K) to 5.30 eV (390–450 K), and then to 5.7 eV (≥450 K) at 0.1 mbar O2 pressure. Oxygen population in the sub-surfaces imparts crucial modifications to Ag at 390–450 K; it makes the surface to be electron-deficient that relates to the change in the WF of Ag and facilitates the formation of space charge layer on Ag surface. Oxygen adsorbed on such modified Ag-surfaces is electrophilic in nature, and this appears at a higher binding energy in core level XPS than the chemisorbed oxygen on metallic Ag. This is supported by angle-dependent NAP-XPS studies. The subsurface population of oxygen in Ag no longer persists at >410 K when the O2 supply is removed. A high ratio of antibonding/bonding O 2p bands suggests the unique silver-oxygen interaction under the measurement conditions.
Keywords: Electronic Structure; epoxidation; heterogeneous catalysis; Surface Science

Epoxidation of karanja (Millettia pinnata) oil methyl esters in the presence of hydrogen peroxide over a simple niobium-containing catalyst - Scotti, Nicola; Ravasio, Nicoletta; Evangelisti, Claudio; Psaro, Rinaldo; Penso, Michele; Niphadkar, Prashant S.; Bokade, Vijay V.; Guidotti, Matteo (Catalysts, 2019)
The synthesis, characterization and catalytic performance of a conceptually simple, novel NbOx-SiO2 catalyst are here described. The niobium(V)-silica catalyst was prepared starting from cheap and viable reactants, by alkaline deposition of NH4Nb(C2O4)(2)H2O in the presence of fructose as a stabilizer and subsequent calcination. The NbOx-SiO2 solid (0.95 Nb wt.%) was tested in the liquid-phase epoxidation with aqueous hydrogen peroxide of methyl oleate, as a model substrate. It was then tested in the epoxidation of a mixture of methyl esters (FAMEs) obtained by transesterification with methanol and purification of karanja oil, extracted from the autochthonous Indian variety of Millettia pinnata tree. The catalyst showed a promising performance in terms of methyl oleate conversion (up to 75%) and selectivity to epoxide (up to 82%). It was then tested on the FAME mixture from karanja oil, where interesting conversion values were attained (up to 70%), although with lower selectivities and yields to the mixture of desired epoxidized FAMEs. The solid withstood four catalytic cycles overall, during which a non-negligible surface reorganization of the Nb(V) sites was observed. However, this restructuring did not negatively affect the performance of the catalysts in terms of conversion or selectivity.
Keywords: epoxidation; fatty acid methyl esters; heterogeneous catalysis; Hydrogen peroxide; karanja oil; mesoporous silica catalyst; Millettia pinnata; niobium catalysts

Nature of electrophilic oxygen: insights from periodic density functional theory investigations - Kenge, Nivedita; Pitale, Sameer; Joshi, Kavita (Surface Science, 2019)
Increasing demand of ethylene oxide and the cost of versatile chemical ethene has been a driving force for understanding mechanism of epoxidation to develop highly selective catalytic process. Direct epoxidation is a proposed mechanism which in theory provides 100% selectivity. A key aspect of this mechanism is an electrophilic oxygen (O-ele) species forming on the Ag surface. In the past two and half decades, large number of theoretical and experimental investigations have tried to elucidate formation of O-ele, on Ag surface with little success. Equipped with this rich literature on Ag-O interactions, we investigate the same using periodic DFT calculations to further understand how silver surface and oxygen interact with each other from a chemical standpoint. Based on energetics, Lowdin charges, topologies and pdos data described in this study, we scrutinize the established notions of O-ele. Our study provides no evidence in support of O-ele, being an atomic species nor a diatomic molecular species. In fact, a triatomic molecular species described in this work bears multiple signatures which are very convincing evidence for considering it as the most sought for electrophilic entity.
Keywords: Ag(100); DFT; Electrophilic; epoxidation; Nucleophilic oxygen

Size-controlled cobalt ferrite nanocrystals: magnetically separable reusable nanocatalysts for selective oxidation of styrene - Jeyavani, Vijayakrishnan; Pawar, Sayali; Dadwal, Arun; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (ChemistrySelect, 2019)
Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes similar to 6 nm and similar to 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of the CFO NCs were highly dependent on the length of fatty acid hydrophobic chain. Corresponding changes of the magnetic properties were investigated by measuring magnetization as a function of field and temperature, which suggest that the CFO NCs were superparamagnetic in nature. The catalytic properties for the oxidation of styrene in organic medium were examined by using the synthesized CFO NCs with sizes similar to 6 nm and similar to 4 nm. The synthesized CFO NCs, well dispersible in organic media, were demonstrated to be highly catalytically active, reached 100% conversion of styrene in 12 h with similar to 77% and similar to 82% selectivity for styrene oxide respectively. The magnetic CFO nanocatalysts were easily separated and recovered from the reaction medium by an external magnet, and reused for several cycles without losing catalytic selectivity for styrene oxide.
Keywords: Cobalt ferrite; epoxidation; Fatty acids; magnetic properties; nanocrystals

Role of facet in the competitive pathway of ethylene epoxidation - Nair, Aathira; Kenge, Nivedita; Joshi, Kavita (Surface Science, 2022)
Ethylene epoxide (EtO) is used as raw material for a broad range of products from pharmaceuticals and plastics to paints and adhesives. Although the reaction of ethylene interacting with preadsorbed oxygen on Ag surface is known for decades, the underlying mechanism of EtO formation is not completely understood. Successful investigation of oxametallacycle (OMC) intermediate common to selective as well as non-selective pathways has ensured at least 50% selectivity. The current study brings out the electronic signatures of distinct conformers of OMC stabilised on two different facets of Ag viz. (100) and (111). There are subtle differences between OMC conformers observed on these two facets with near-eclipsed on Ag(100) and near-staggered on Ag(111). A detailed analysis of Ag-O, C-O, C-C, and Ag-C interactions along with projected Density of States (pDOS) and projected Crystal Orbital Hamilton Population (pCOHP) imply towards ring closure on Ag(100) and hydrogen transfer on Ag(111). Finally, our understanding based on electronic and structural signatures are backed up by activation barriers computed through NEB calculations. Activation barrier for EtO is lower on (100) as compared to (111) facet. Thus, our study sheds light on how these differences between OMC affect the selectivity towards EtO.
Keywords: Ag(100); Ag(111); DFT; epoxidation; Ethylene Oxide (EtO); OMC

Efficient olefin epoxidation with high turnover rates over ordered mesoporous silica nanoparticles with uniform manganese sites - Negi, Sanjay Singh; Khatri, Prateek; Singh, Anand Pal (Microporous and Mesoporous Materials, 2023)
Olefin epoxidation has been studied over a series of mesoporous manganese silicate nanoparticles and tBuOOH. Partial substitution of Si by Mn in silica framework leads to highly dispersed, distorted Mn(III) sites, confirmed by various physicochemical analyses. High conversion and stable styrene oxide, stilbene oxide and epoxy cyclohexane yield have been achieved with MS75 with 1:1.5 ratio of olefin: oxidant. However, at faster reaction rates lower styrene oxide yield is observed at lower Mn-containing catalyst (MS100). High TON, TOF over manganese sites shows accessible monomeric Mn sites. Attributed to high reactant density at redox-active Mn silicate sites due to facile diffusion across shallow pore depth channels of nanoparticulate om-MSx and surface hydrophobic characteristics. The catalysts were found to be stable under recycling and filtration experiments. The excellent stability against leaching of active manganese species indicates stable sites and good textural properties in om-MSx, essential for extended activity.
Keywords: epoxidation; Manganese silicates; Mesoporous silica nanoparticles; Ordered mesoporous silica; pH adjustment